Pengaruh Budaya Organisasi dan Motivasi Kerjaterhadap Loyalitas Karyawan di Rumah Makan dan RestoranPak Nurdin Kota Pekanbaru – Riau - La Ode Syarfan (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of organizational culture and work motivation on employee loyalty at Pak Nurdin Restaurant and Eatery in Pekanbaru City, Riau Province. The research method used was a quantitative descriptive survey with a population of 49 employees who had worked for more than one year, with a sample size of 37 respondents determined using the Slovin formula and simple random sampling techniques. Data collection was conducted using a Likert-scale questionnaire supplemented by interviews and observations. Data analysis used validity and reliability tests, classical assumption tests, and multiple linear regression analysis supplemented by t-tests, F-tests, and coefficients of determination. The results showed that organizational culture had a positive and significant effect on employee loyalty, as evidenced by the calculated t-value of 3.375, which is greater than the t-table value of 1.985, and a significance level of 0.001, which is less than 0.05. Furthermore, work motivation also had a positive and significant effect on employee loyalty, with a calculated t-value of 8.410, greater than the t-table of 1.985, and a significance level of 0.000. Therefore, work motivation was the most dominant variable. Simultaneously, organizational culture and work motivation significantly influenced employee loyalty, contributing 73.9 percent. The conclusion of this study indicates that strengthening a positive organizational culture and continuously increasing work motivation are important strategies for increasing employee loyalty and maintaining the sustainability of restaurant businesses.   Keywords: Organizational Culture, Work Motivation, Employee Loyalty, Restaurants, Human Resource Management